Oxygen-rich microporous carbons with exceptional hydrogen storage capacity - Blankenship, Troy Scott; Balahmar, Norah; Mokaya, Robert (Nature Publishing Group, 2017)
Porous carbons have been extensively investigated for hydrogen storage but, to date, appear to have an upper limit to their storage capacity. Here, in an effort to circumvent this upper limit, we explore the potential of oxygen-rich activated carbons. We describe cellulose acetatederived carbons that combine high surface area (3800 m2 g-1) and pore volume (1.8 cm3 g-1) that arise almost entirely (> 90%) from micropores, with an oxygen-rich nature. The carbons exhibit enhanced gravimetric hydrogen uptake (8.1 wt% total, and 7.0 wt% excess) at -196 ºC and 20 bar, rising to a total uptake of 8.9 wt% at 30 bar, and exceptional volumetric uptake of 44 g l-1 at 20 bar, and 48 g l-1 at 30 bar. At room temperature they store up to 0.8 wt% (excess) and 1.2 wt% (total) hydrogen at only 30 bar, and their isosteric heat of hydrogen adsorption is above 10 kJ mol-1.